Results of Expedicion Humana. I. Analysis of HLA class II (DRB1-DQA1-DPB1) alleles and DR-DQ haplotypes in nine Amerindian populations from Colombia (2022)
eng: HLA class II variation was analyzed in nine Native American populations of Colombia using PCR/SSOP typing methods. Under the auspices of the Expedition Humana, approximately 30 unrelated native Colombia Indian samples each from the Tule (NW Pacific Coast), Kogui (Sierra Nevada). Ijka (Sierra Nevada), Ingano (Amazonas), Coreguaje (Amazonas), Nukak (Amazonas), Waunana (Pacific), Embera (Pacific) and Sikuani (Northeastern Plains) were collected and analyzed at the DRBI, DQA1, DQB1 and DPB1 loci. The number of different DRB1, DQA1, DQB1 and DPB1 alleles in the Colombian Indians is markedly reduced in comparison with neighboring African Colombian populations, which exhibit a very high degree of class II variability, as discussed in an accompanying paper. In the Colombian Amerindian groups, DR2 (DRB1*1602), DR4 (DRB1*0407, *0404, *0403 AND *0411), DR6 (DRB1*1402) and DR8 (DRB1*0802) comprise > 95% of all DRB1 alleles. We also found an absence of DR3 in all populations, and DR1, DR7 and DR9 allelic groups were either very rare or absent. Each Colombian Amerindian population has a predominant DRB1 allele (f = approximately 0.22-0.65) and DRB1-DQA1-DQB1 haplotype. Several novel DR-DQ haplotypes were also found. At the DPB1 locus, DPB1*0402 (f = 0.28-0.82), *1401 (f = 0.03-0.45), and *3501 (f = 0.03-0.27), were the three most prevalent alleles, each population maintaining one of these three alleles as the predominant (f > 0.26) DPB1 allele. The reduction of diversity for the HLA class II alleles in the Colombian Indians is suggestive of a population bottleneck during the colonization of the Americans, with little to no subsequent admixture with neighboring African Colombian populations in the last approximately 300 years.